The Excitement of Change-A Book of Personal Growth - Varghese Manickanamparampil (Journal of Dharma, 2020)
Benjamin V. White and Helen White, authors of The Excitement of Change—A Book of Personal Growth attempt to share with readers a large number of true-life experiences which people have gone through on their onward march to a new and fuller life. This new life is attained only through a real change, which is an inward experience. This experience usually begins in a period of crisis.